Habbatussauda Obat Segala Penyakit Yang di Sabdakan Rasulullah SAW: Habbatussauda Obat Segala Penyakit Yang di Sabdakan Rasulullah SAW - sofiannisa, rima (LPPM STIKes Muhammadiyah Ciamis, 2022)
With advances in technology and information, Muslims should be able to carry out renewals in conducting studies on hadiths regarding and related to health, especially during the pandemic, namely covid-19. And one of the treatments contained in the hadith that the Messenger of Allah (saw) said is Black Seed which has a lot of content which is useful for increasing immunity.